ASEAN PLUS THREE EMERGENCY RICE RESERVE (APTERR): An Analysis on Its Role to The ASEAN Food Security in The Global Pandemic - Napitupulu, Sanggam Maruli (Universitas Sebelas Maret, 2021)
ASEAN Plus Three Emergency Rice Reserve or APTERR is a rice bank cooperation between ASEAN member states as well as China, South Korea, and Japan (as +3 or Plus Three). This collective commitment is made in order to ensure food security, particularly in the form of rice, in their member countries. Initiated due to the crisis that occurred from 2007 to 2011, APTERR is now facing the global COVID-19 pandemic that has been going on for more than one year. This, of course, presents a threat to the availability of rice due to limited mobility in the production or distribution sector, while the needs of rice in the community remains the same. In this paper, we will discuss further efforts and actions that have been taken by APTERR in assisting ASEAN members who are in an emergency status in their availability of rice. The research method which this paper used is a literacy review method, which will provide facts related to the background of APTERR, problems that threaten the threat of rice in the ASEAN region, and the latest presentation data to answer whether or not the APTERR plan will succeed in overcoming this pandemic crisis.